EFL PRE-SERVICE TEACHERS’ EXPERIENCES DOING PRACTICUM DURING COVID-19 PANDEMIC - Janika Sri Ayumi; Yanti Sri Rezeki; Wardah Wardah (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
This study aims to identify the experiences of EFL pre-service teachers doing practicum during the COVID-19 pandemic. Six participants in this case study. They were the eighth-semester students of English education study program at the University of Tanjungpura. They have spent three years studying in the English department and have finished micro-teaching and Introduction to School Field (PLP) II course. Data from this study were collected using semi-structured interviews and document analysis. The data were analyzed based on Miles and Huberman’s model, including data reduction, and the gained data were displayed and concluded. The result showed that EFL pre-service teachers admitted that although it is easy to use the online system, they sometimes have problems in terms of internet connection and electronic devices. External factor, such as lack of motivation during the teaching practicum, hindered the pre-service teachers. Pre-service teachers can overcome their problems by having preparation before teaching practice and using various learning strategies to stimulate the students, such as games, icebreakers, or quizzes. The EFL pre-service teachers also consulted with their supervisors and in-service teachers to solve their problems during teaching practicum progress